Lexical Bootstrapping 2013
DOI: 10.1515/9783110308693.165
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of lexical, grammatical, phonetic and phonological development in German late talkers – A longitudinal study

Abstract: Late Talkers (= LTs) are identified at the age of two on the basis of their restricted language skills regarding expressive lexicon and are at risk for Specific Language Impairment (= SLI). SLI-children especially show deficits in the area of grammar, but also in the area of phonology. Receptive language, phonetic and phonological abilities are seen as within language predictors for LTs' outcome. This article addresses the question of whether German LTs show heterotypic continuity in (i) expressive lexicon and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…Previous research has found that TD children show reciprocal relations between lexical and grammatical development, suggesting bidirectional bootstrapping (Dionne et al, 2003). However, this could be different for children whose language abilities are compromised, as suggested by research on late talkers (Moyle, Weismer, Evans, & Lindstrom, 2007;Schlesiger, 2013). Moyle et al showed that children with TD exhibited patterns consistent with lexical bootstrapping until age 2 years and 6 months (2;6) while patterns consistent with syntactic bootstrapping were observed from age 2;6 until 3;6.…”
Section: Reciprocal Relationships: Syntactic and Lexical Bootstrappingmentioning
confidence: 98%
“…Previous research has found that TD children show reciprocal relations between lexical and grammatical development, suggesting bidirectional bootstrapping (Dionne et al, 2003). However, this could be different for children whose language abilities are compromised, as suggested by research on late talkers (Moyle, Weismer, Evans, & Lindstrom, 2007;Schlesiger, 2013). Moyle et al showed that children with TD exhibited patterns consistent with lexical bootstrapping until age 2 years and 6 months (2;6) while patterns consistent with syntactic bootstrapping were observed from age 2;6 until 3;6.…”
Section: Reciprocal Relationships: Syntactic and Lexical Bootstrappingmentioning
confidence: 98%
“…Entwicklungszusammenhänge zwischen expressiven lexikalischen Fähigkeiten und grammatischen Leistungen, die hier grob durch die Äußerungs-länge eingeschätzt wurden, sind für sprachverzögerte und sprachu nauffällige Kinder im 3. Lebensjahr bekannt ( [33,[37][38][39]) und zeigten sich in der vorliegenden Studie auch für Kinder zwischen 3 und 6 Jahren im Kontext des Erzählens. Obwohl die Äußerungen der sprachauffälligen Kinder kürzer waren, enthielten sie ein ähnliches Repertoire an Wortarten, wobei subtile Unterschiede auf eine geringere Qualität der Wortartenkomposition hinweisen: Pronomen, die für die Herstellung textgrammatischer Zusammenhänge, insbesondere für die Wiederaufnahme von eingeführten Referenten notwendig sind, wurden seltener verwendet, während Nomen und personal-soziale Wörter, die typisch für frühe Phasen des Lexikonerwerbs sind, stärker vertreten waren als bei sprachunauffälligen Kindern.…”
Section: Diskussion ▼unclassified